Naturalistic Evaluation of Programs. Parents' Voice in Parent Education Programs - Ştefan COJOCARU; Daniela COJOCARU (Transylvanian Review of Administrative Sciences, 2011)
The study presents some practical means for carrying out a naturalistic evaluation, a process that has resulted, for instance, in the identification of the profile of the parent educator as defined by the parents attending parent education classes as part of the program “How to become better parents”, implemented by Holt Romania with the support of UNICEF Country Office. Exploring parents’ voices is an advantage in naturalistic evaluation when trying to identify some essential aspects of the program. Based on the grounded theory strategy, this study explores the participants’ subjective representations, being a useful source of information for future development of similar programs. The profile of the parent educator as defined by the parents has several significant characteristics: the educator’s ability to reduce power asymmetry and increase responsiveness, the importance of the educator’s personal traits of character, the role of social and spatial proximity, the importance of the parent educator in personalizing the relationship with institutions etc. The results highlight the ways in which parent educator’s characteristics can significantly contribute to increasing the attendance of such programs.